Analisis Pengelolaan Dana Desa Dalam Pembangunan Di Kampung Waena Distrik Heram Kota Jayapura Tahun 2019-2021 - Ester Rosalina Komboy; Transna Putra Urip; Sarlota A. Ratang (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2022)
The study's objectives are as follows: 1) to determine the level of village fund management in Waena Village from 2019 to 2021. 2) To find out the achievements of the village fund management and also find out the challenges and obstacles faced by the Waena village government in realizing the village funds for the welfare of the Waena village community. The types of research used are quantitative and qualitative, and the data collection techniques used are observation, documentation, literature study, interviews, and questionnaires. However, the effectiveness ratio and qualitative descriptive analysis are also used in the form of exposure to the results of interviews and questionnaires. The results of this study indicate that: 1) The realization of village funds is estimated together with the 2019 target of reaching 91% or "effective," in 2020 reaching 94% or "effective," and in 2021 reaching 100% or "very effective." Then, for the obstacles found in this study, there are unexpected conditions such as the COVID virus outbreak, weather, and others, as well as community support that is still very limited, communication with the people, and so on. Keywords: Village, Village Fund Management (DD), Effectiveness